An investigation into the synergistic association between the major Clostridium cellulovorans cellulosomal endoglucanase and two hemicellulases on plant cell wall degradation - Beukes, Natasha (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2008)
The cellulosome is a multimeric enzyme complex that has the ability to metabolise a wide variety of carbonaceous compounds. Cellulosomal composition may vary according to the microbe's nutritional requirement and allows for the anaerobic degradation of complex substrates. The complex substrates of interest in this research study were sugarcane bagasse and pineapple fibre waste, as they represent two important lignocellulosic, South African agricultural crops. The effective degradation of complex plant biomass wastes may present a valuable source of renewable compounds for the production of a variety of biofuels, for example bioethanol, and a variety of biocomposites of industrial importance. The identification of renewable energy sources for the production of biofuels is becoming increasingly important, as a result of the rapid depletion of the fossil fuels that are traditionally used as energy sources. An effective means of completely degrading lignocellulose biomass still remains elusive due to the complex heterogeneity of the substrate structure, and the fact that the effective degradation of the substrate requires a consortium of enzymes. The cellulosome not only provides a variety of enzymes with varying specificities, but also promote a close proximity between the catalytic components (enzymes). The close proximity between the enzymes promotes the synergistic degradation of complex plant biomass for the production of valuable energy products. Previous synergy studies have focused predominantly on the synergistic associations between cellulases; however, the synergy between hemicellulases has occasionally been documented. This research project established the synergistic associations between two Clostridium cellulovorans hemicellulases that may be incorporated into the cellulosome and a cellulosomal endoglucanase that is conserved in all cellulosomes. This research study indicated that there was indeed a synergistic degradation of the complex plant biomass (sugarcane bagasse and pineapple fibre). The degrees of synergy and the ratio of the enzymes varied between the two complex substrates. The initial degradation of the bagasse required the presence of all the enzymes and proceeded at an enhanced rate under sulphidogenic conditions; however, there was a low production of fermentable sugars. The low quantity of fermentable sugars produced by the degradation of the bagasse may be related to the chemical composition of the substrate. The sugarcane contains a high percentage of lignin forming a protective layer around the holocellulose, thus the glycosidic bonds are shielded extensively from enzymatic attack. In comparison, the initial degradation of the pineapple fibre required the action of hemicellulases, and proceeded at an enhanced rate under sulphidogenic conditions. The initial degradation of the pineapple fibre produced a substantially larger quantity of fermentable sugars in comparison to the bagasse. The higher production of fermentable sugars from the degradation of the pineapple fibre may be explained by the fact that this substrate may have a lower percentage of lignin than the bagasse, thus allowing a larger percentage of the glycosidic bonds to be exposed to enzymatic attack. The data obtained also indicated that the glycosidic bonds from the hemicellulosic components of the pineapple fibre shielded the glycosidic bonds of the cellulose component. The identification of the chemical components of the different substrates may allow for the initial development of an ideal enzyme complex (designer cellulosome) with enzymes in an ideal ratio with optimal synergy that will effectively degrade the complex plant biomass substrate.
Keywords: Clostridium; Cellulose; Hemicellulose; Cellulase; Biomass conversion; Biomass energy -- South Africa; Energy crops -- South Africa; Bagasse -- Biodegradation; Pineapple -- Biodegradation